2020
DOI: 10.3390/genes11020224
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Genome Maintenance by the Multifunctional PIF1 DNA Helicase Family

Abstract: The two PIF1 family helicases in Saccharomyces cerevisiae, Rrm3, and ScPif1, associate with thousands of sites throughout the genome where they perform overlapping and distinct roles in telomere length maintenance, replication through non-histone proteins and G4 structures, lagging strand replication, replication fork convergence, the repair of DNA double-strand break ends, and transposable element mobility. ScPif1 and its fission yeast homolog Pfh1 also localize to mitochondria where they protect mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 196 publications
(262 reference statements)
0
35
0
1
Order By: Relevance
“…Note that Ctf4 and Mrc1 are components of the RPC and are known to affect fork stability ( 46–48 ). The accessory helicase Rrm3 removes obstacles in front of the replisome ( 17 , 49 ). Consistently, it appeared that dCas9-induced replication fork stalling was enhanced in the rrm3 Δ strain compared to the wild-type strain (Figure 5B and Supplementary Figure S4E–G ).…”
Section: Resultsmentioning
confidence: 99%
“…Note that Ctf4 and Mrc1 are components of the RPC and are known to affect fork stability ( 46–48 ). The accessory helicase Rrm3 removes obstacles in front of the replisome ( 17 , 49 ). Consistently, it appeared that dCas9-induced replication fork stalling was enhanced in the rrm3 Δ strain compared to the wild-type strain (Figure 5B and Supplementary Figure S4E–G ).…”
Section: Resultsmentioning
confidence: 99%
“…Pif1 is a 5′–3′ helicase with roles in telomere length regulation, Okazaki fragment processing, unwinding of G-quadruplex structures, DNA repair, disassembly of stalled replication complexes, and 5′ end resection (reviewed in Dewar and Lydall, 2012 ; Chung, 2014 ; Muellner and Schmidt, 2020 ). Pif1 also facilitates mitochondrial DNA replication; yeast without Pif1 are respiration incompetent ( Foury and Kolodynski, 1983 ).…”
Section: Regulation Of De Novo Telomere Additionmentioning
confidence: 99%
“…Misregulated G4 structures or G4 structures formed at the wrong time or location can lead to genome instability. Different experimental approaches have shown that G4 formation can alter transcription, translation and the activity of polymerases and telomerase (Bochman et al 2012 ; Rhodes and Lipps 2015 ; Muellner and Schmidt 2020 ; Varshney et al 2020 ). In summary, misregulated G4 structures lead to a stalled or slowed DNA replication machinery and increase the number of chromosomal mutations, deletions and recombination events (Valton and Prioleau 2016 ; Bryan 2019 ; Lerner and Sale 2019 ).…”
Section: Introductionmentioning
confidence: 99%